The COVID-19 Pandemic Outbreak Impact And Prevention From Legal Perspective : An Indonesian Experience - Cindy Kang; Hari Sutra Disemadi (Universitas Internasional Batam, 2021)
The COVID-19 pandemic affected various aspects such as economy, health, environment, and others. The pandemic that occurred in Indonesia gave a huge responsibility to the government as stated in the fourth paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia. Everything that happens in handling this pandemic has a close relationship with the law, including human rights due to the large number of people who have died, regional quarantine, and the protection and guarantee of work safety for health workers who are at the frontline dealing with this pandemic. This research uses normative legal research methods